(untitled) (Journal of Parents and Teachers, 2023)
This article addresses how blind people develop all the other senses, leaning on them to make up for their lack of vision. The author, based on her own experience, reports some events in which this is clear. Being touch and hearing the ones that awake imagination in order to know how the world around her is.